EARLY-AGE MARRIAGE IN PERSPECTIVE OF INDONESIAN ISLAMIC FAMILY LAW - ., Nashuddin; Tahir, Masnun (Al-Mawarid Jurnal Hukum Islam, 2015)
The article below tries to describe early age marriage according to contemporary Islamic Family law. Actually the substance of Islamic family law is to create a social merit for people in the present and the future. Islamic law is humane and always brings mercy to the world. It intends to make the Islamic law remain up to date, relevant and able to respond to the dynamics of the times. The government prohibits early-age marriages by several considerations. Even though, the religion does not limit the age of marriages, but it also has a positive value. Such a problem is quite a dilemma. Therefore, in such a context Islam is a mercy to the universe, including Indonesia, the grounding of Islamic law in the faces that follow the movement of the people of Indonesia to follow the motion flow of the Indonesian people to be a necessity. Thus, in the view of the author, in the Indonesian context, the grounding of values of Islamic law, or, more precisely, the adaptation of Islamic law in the social change of Indonesian people. It can be used as a counter towards the practice of early-age marriages that are in fact still be mistaken by most Indonesian society. Thus, the assumption that early-age marriages are permitted by religion but not permitted under the law is wrong and is the form of ignorance about the history of the building concept of the establishment of syariâah law in general, the history and formation as well as the enactment of the Act No. 1 in 1974 in particular, as well as the understanding and dissemination of the concept and application of the Indonesian Fiqh. Keywords : Marriage, Early Age, Islamic Family Law, Contemporary, and Indonesia.